KONSEP VOLUNTARISME DALAM GERAKAN SAMIN TOLAK PABRIK SEMEN - Enkin Asrawijaya (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2021)
The Kendeng Mountains, which are rich of limestone, clay, spring and other varying mining sources, are a strategic choice for establishing a cement factory. The plan to establish a cement factory was supported by government but was opposed by the Samin community along with Kendeng farmers. This study aims to discuss the resistance of the Samin (Sedulur Sikep) indigenous people to extractive companies. To discuss this article, we need a theory that can be used to analyze how these volunteers grow and work. This theory is Parsons’ volunteer Action theory. Meanwhile, the research method used was an ethnographic approach. The results showed that the strength gained by the Samin community is the awareness of striving to uphold the maturity of its members through the spirit of a volunteer. This voluntary spirit is developed by cultivating farmer solidarity. Some actors have good rhetorical abilities so that the JMPPK is established to move with an active and open line of resistance.